Properties and applications of Magnetorheological fluids - A. Spaggiari (Fracture and Structural Integrity)
This brief introduction describes the mechanical, rheological and magnetic properties of the magnetorheological (MR) fluids for feasible engineering applications. The typical modes of exploiting this technology are shown and discussed. An increasing number of industrial applications illustrate how the MR fluids peculiar properties may be used to provide optimal performance in semi active damping and dissipative devices.